Studi Perilaku (Aktivitas Harian) Monyet Ekor Panjang (Macaca fascicularis) di Taman Nasional Kelimutu, Kecamatan Kelimutu, Kabupaten Ende, Provinsi Nusa Tenggara Timur - Wilhelmiana Djaga; Mamie E Pelondo'u; Maria M. E. Purnama (Wana Lestari, 2020)
Long-tailed monkeys (Macaca fascicularis) are non-human primates that live in groups and are inextricably linked to social interactions between individuals in a population and cause many different activities. Activities that occur can indicate the use and feasibility of the habitat and the distribution of the niche by each long-tailed macaque (Macaca fascicularis). The Kelimutu National Park is one of the habitats of long-tailed macaques (Macaca fascicularis), one of the efforts to preserve the population of long-tailed monkeys (Macaca fascicularis) in natural habitats. This study is designed to determine the daily behavior of long-tailed macaques (Macaca fascicularis) and was carried out from July to August 2019 in Kelimutu National Park, Kelimutu District, late Regency, East Nusa Tenggara Province. Observation and data acquisition are carried out according to the focal point method and the ad libitum method with a recording duration of 5-10 minutes. After the data is obtained, it is analyzed descriptively and the percentage of daily activity of long-tailed macaques (Macaca fascicularis) is calculated using the frequency percentage formula. The results showed that the activities that were frequently performed by long-tailed macaques (Macaca fascicularis) moved with 35% presentation, followed by 24% feeding activity, 22% nursing activity, 9% rest activity, 7% social activity and 3% agonistic activity.